1997
DOI: 10.1136/pgmj.73.864.640
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide treatment for insulinoma: a national UK survey

Abstract: SummaryA survey of UK patients receiving the drug diazoxide, revealed 40 patients with insulinoma on this treatment. Mean age (±SD) was 67+18 years, and 74% were female. Duration of treatment was 7+6 years (range 1-22). Most (55%) patients were treated with diazoxide because of tumour non-localisation (including failed previous surgery). Metastatic disease (20%) and poor surgical risk (10%) were other indications. Side-effects (notably fluid retention and hirsutism) were common (47%) but not troublesome. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
1
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 4 publications
(1 reference statement)
0
102
1
11
Order By: Relevance
“…20 Some patients have gastrointestinal intolerance to the drug and in very high doses it may produce anorexia. 21 We have found that a small initial dose with an increase of Յ 300 -400 mg per day over 3-4 weeks is the most effective way to initiate and maintain therapy. All the other forms of therapy shown in Table 2 have either had no benefit or relatively short-term benefit and most, such as chemotherapy regimens, are toxic and of little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…20 Some patients have gastrointestinal intolerance to the drug and in very high doses it may produce anorexia. 21 We have found that a small initial dose with an increase of Յ 300 -400 mg per day over 3-4 weeks is the most effective way to initiate and maintain therapy. All the other forms of therapy shown in Table 2 have either had no benefit or relatively short-term benefit and most, such as chemotherapy regimens, are toxic and of little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Recent recommendations suggest the use of everolimus as an alternative to chemotherapy as the first line of antitumor systemic therapy in the case of progressive malignant insulinomas (31). Diazoxide therapy is the oldest antisecretory medical option that is still largely prescribed, even if data are lacking regarding the duration of its benefit and tolerance in the long run in malignant insulinoma (32,33). Somatostatin analog efficacy in the control of hypoglycemic symptoms has also been reported in malignant insulinoma, mainly in case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Oversecretion of insulin from insulinomas can usually be treated by a combination of somatostatin and diazoxide. 28,29 Diazoxide has also been used to "rest" β-cells in newly diagnosed type 1 diabetics and demonstrated a persistent effect in preserving a small fraction of functional β-cells that would have been lost without treatment. 12,30 However, the use of diazoxide is fraught with side effects, probably due to its low Kir6.2/SUR1 selectivity.…”
Section: Discussionmentioning
confidence: 99%